Physicochemical composition and sensory quality of goat meat burgers. Effect of fat source - Teixeira, Alfredo (2018)
Several strategies for producing healthier meat products have been developed. Reducing fat content, using different fat sources, modifying and improving the fatty acid profile or even replacing saturated fat with oleogels are some of the methods used. Goat meat mainly from animals out of quality brands with low commercial value can be valorized when processed, giving the opportunity to increase its consumption and acceptability. Thus, the aim of this study was to study the effect of the replacement of pork as a source of fat with an olive oleogel in burgers manufactured with goat meat and to compare the goat meat burgers with the most common commercial burgers made with beef. Two replications of the burgers were manufactured at different times, and three samples of each burger type (GOO—goat meat burgers with olive oil; GPF—goat meat burgers with pork fat) were randomly selected from each lot manufactured. Each sample was analyzed in triplicate for each physicochemical analysis. At the time, the manufactured burgers were analyzed simultaneously with the commercial burgers. The burgers with olive oil (GOO) showed higher a* and b* than the burgers with pork fat (GPF) and consequently had lower h° and C*. The ashes, protein and collagen contents of the GOO and GPF burgers were similar to those of the other goat meat products. The effect of the incorporation of oleogel on the physicochemical composition of the burgers in relation to the pork fat was expressed in the fat content, 4 and 2.78% for GOO and GPF, respectively. CH burgers have significantly higher fat content (13.45%) than GOO and GPF burgers. The replacement of pork backfat with a vegetable oleogel modified the fatty acids profile, since the GOO burgers had the highest MUFA and PUFA and the lipidic quality, defined by the IA and IT indices, was 0.38 and 0.99, respectively. Globally, goat burgers were sensorially harder and presented a more difficult chewiness than CH. The replacement of the pork back fat with oleogel significantly decreased hardness and chewiness.